PERBEDAAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL STUDENT TEAM ACHIVEMENT DIVISION (STAD) DAN NUMBERED HEAD TOGETHER (NHT) PADA MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN KELAS VIII DI SMP N 6 LANGSA TAHUN PELAJARAN 2019/2020 - Kartini, Kartini; Nursamsu, Nursamsu (Department of Biology Education, Faculty of Teacher Training and Education, Samudra University, 2020)
Abstract Education is the process of changing the attitudes and behavior of a person or group who in an effort to mature themselves through teaching and education efforts, when talking about education people will tend to think about school or tertiary education, even though the notion of education is not only related to school, but also regarding grades students. This study aims to determine differences in student learning outcomes and which model is better for learning outcomes using the Student Team Achievement Division (STAD) and Numbered Head Together (NHT) models on the structure and function material of plant networks in class VIII at SMP N 6 Langsa. 2019/2020 lessons. The method used is an experimental method with instruments in the form of written tests. The results obtained prove that there is a comparison of the Student Team Achievement Division (STAD) model with Numbered Head Together on the learning outcomes of class VIII students at SMP N 6 Langsa in the 2019/2020 school year, with the testing criteria -t_ (1-1 / 2 α) <t <t_ (1-1 / 2 α) with a value of -2.008 - 0.025≤ 5.97 ≤ 2.008 - 0.025 is the same as -2.033 ≤ 5.79 ≤ 1.983. With a difference in the comparison of learning outcomes of 2.46. Material for the structure and function of plant tissue for class VIII at SMP N 6 Langsa in the 2019/2020 school year.